China and India in the age of globalization - Sharma, Shalendra D., 1958- (Cambridge ; New York : Cambridge University Press, 2009)
"The rise of China and India is the story of our times. The unprecedented expansion of their economic and power capabilities raises profound questions for scholars and policy makers. What forces propelled these two Asian giants into global pacesetters, and what does their emergence mean for the United States and the world? With intimate detail, Shalendra D. Sharma's China and India in the Age of Globalization explores how the interplay of sociohistorical, political, and economic forces has transformed these once poor agrarian societies into economic powerhouses. Yet globalization is hardly a seamless process, because the vagaries and uncertainties of globalization also present risks and challenges. This book examines the challenges both countries face and what each must do to strike the balance between reaping opportunities and mitigating risks.
For the United States, assisting a rising China to become a responsible global stakeholder and fostering peace and stability in the volatile subcontinent will be paramount in the coming years."--BOOK JACKET.
Prelude to globalization : China (1949-78) and India (1947-91) -- China and India embrace globalization -- China : strategies and patterns of global integration -- India : strategies and patterns of global integration -- Sino-Indian relations : partners, friends or rivals? -- India and the United States : from estrangement to engagement -- The rise of China and its implications for the United States -- China and India : future challenges and opportunities.
Includes bibliographical references and index.
Keywords: Globalization -- China; Globalization -- India; China -- Economic conditions -- 1949-; China -- Economic policy -- 1949-; India -- Economic conditions -- 1947-; India -- Economic policy -- 1947-; China -- Relations -- India; India -- Relations -- China